Transcriptional Alterations of Virulence-Associated Genes in Extended Spectrum Beta-Lactamase (ESBL)-Producing Uropathogenic Escherichia coli during Morphologic Transitions Induced by Ineffective Antibiotics - Demirel, Isak; Rangel, Ignacio; Petersson, Ulrika; Persson, Katarina; Kruse, Robert (Frontiers in Microbiology, 2017)
It is known that an ineffective antibiotic treatment can induce morphological shifts in uropathogenic Escherichia coli (UPEC) but the virulence properties during these shifts remain to be studied. The present study examines changes in global gene expression patterns and in virulence factor-associated genes in an extended spectrum beta-lactamase (ESBL)-producing UPEC (ESBL019) during the morphologic transitions induced by an ineffective antibiotic and in the presence of human primary bladder epithelial cells. Microarray results showed that the different morphological states of ESBL019 had significant transcriptional alterations of a large number of genes (Transition; 7%, Filamentation; 32% and Reverted 19% of the entities on the array). All three morphological states of ESBL019 were associated with a decreased energy metabolism, altered iron acquisition systems and altered adhesion expression. In addition, genes associated with LPS synthesis and bacterial motility was also altered in all the morphological states. Furthermore, the transition state induced a significantly higher release of TNF-α from bladder epithelial cells compared to all other morphologies, while the reverted state was unable to induce TNF-α release. Our findings show that the morphological shifts induced by ineffective antibiotics are associated with significant transcriptional virulence alterations in ESBL-producing UPEC, which may affect survival and persistence in the urinary tract.